Therapeutic engagement: Perspectives from adolescents with eating disorders. Issue 2 (15th December 2015) - Zaitsoff, Shannon; Yiu, Angelina; Pullmer, Rachelle; Geller, Josie; Menna, Rosanne
Abstract: This study aimed to identify factors that adolescents with eating disorders (ED) consider important for therapeutic engagement, and to examine similarities and differences in the number of identified factors considered important for therapeutic engagement based on diagnostic status and readiness and motivation to change dietary restriction behaviors. Treatment seeking adolescent females ( n =34, M age =16.33, SD=1.34) with an ED were prompted to generate responses to 4 constructs related to therapeutic engagement: (1) Trust, (2) Agreement on therapeutic goals, (3) Confidence in Ability to Change and (4) Feelings of Inclusion in therapeutic decisions. A coding scheme for each construct was developed using a random sample of responses, and each category within a construct was rated as present or absent for each participant. Frequencies and percentages of participants who reported each category within each construct are reported. Additionally, findings indicate that the top two out of three categories reported within each construct were the same between participants with AN versus EDNOS, and between participants high and low in readiness and motivation to change dietary restriction behaviors. This study is a first step in identifying aspects of therapeutic engagement that are important to adolescents with ED, which may differ from adults. Highlights: Qualitative responses on therapeutic engagement from adolescent females with eating disorders were coded and defined: (1) trustworthiness, (2) agreement on therapeutic goals, (3) Confidence in Ability to Change and (4) Feelings of Inclusion. Trustworthiness was influenced by a therapist's genuine concern . Perceptions of agreement on therapeutic goals were influenced by Synchrony between client and therapist on therapeutic goals. Confidence in Ability to Change was influenced by therapist support . Feelings of Inclusion in therapeutic decisions were influenced by a client's sense of control over their care.